Integrasi Nilai-Nilai Pendidikan Islam dalam Tradisi Babilang sebagai Penilaian Kecocokan Pernikahan Masyarakat Banjar - Nuril Khasyi'in; Nabhan, Mariani (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
This study examines the integration of Islamic educational values within the Babilangan tradition (a name based compatibility assessment) used by the Banjar Muslim community to evaluate the potential marriage partners. This research applies a qualitative field method, data were collected through interviews with tuan guru (religious teacher) who possess sanad (a chain of knowledge transmision) and individuals who have experienced in the Babilangan process. The findings indicate that the practice is rooted in classical Islamic texts and can only be performed by those with proper scholarly transmisions, not by ordinary people even if they own the book. When unfavorable results arise, solutions are offered by the scholars or explained in the book. The tradition reflects core Islamic educational values such as respect for scholars (ta’zhim), social connectedness (silaturrahim), and charitable giving (sadaqah). As long as the tradition is understtod as a cultural effort (ikhtiar) and not as a way to determine fate. Babilanagn can be seen as a form of local wisdom that aligns with the spirit of Islamic education.